PERCEPTION OF THE LIFE QUALITY OF SWIMMING MÁSTER ATHLETES ABOVE 60 YEARS (Fiep Bulletin - online, 2013)
In accordance with the World Health Organization, the world population keeps moving towards aging and is going to surpass 9 billion people by 2050, following the estimates and projections from the World Population Situation 2006 revision. Brazil will have at about 15.8 million people over 60 years old, in accordance with IBGE. The aim and the relevance of this study are to observe if the master swim activity, for over 60 years old athletes, contributes toward a better life quality for the practitioners and competitors. This work is of a descriptive format and there was no interference on the study object. Twenty eight master athletes, all over 60 years old, from both sexes, active swimmers and participants in State, National and International competitions, long and short pools, were selected for this study. We verified, in the results, that with respect to sensory functioning, past, present and future activities, social participation and in its intimacy, all reached a positive return with the practice of swimming, being more than 60% satisfied. On the other hand, with respect to the result referred to autonomy, at about 44% of the answers appointed to the low level of autonomy in the daily life activities of old athletes.. Therefore, with this study, we may suppose, from its results, that the habit of daily physical activity, with master swimmer athletes, actives over 60 years old, increases the self esteem and life quality for each one of its practitioners.